Effects of partial oxidation of PMAN carbon on their performance as anodes in 1M LiPFsub 6/EC-DMC solutions - Guidotti, R. A. (Sandia National Laboratories, 1996)
A study was undertaken to examine the effects of partial oxidation on the electrochemical performance of carbons derived from poly(methylacrylonitrile) (PMAN)-divinylbenzene (DVB) co-polymers. Mild oxidation was examined as a possible technique to increase the reversible capacity, improve cycleability, and reduce the amount of irreversible capacity associated with the formation of the passivation layer during the first reduction. Oxidizing conditions involved treatment of the PMAN carbon prepared at 700 C with dry COsub 2 or with steam at 600 C for one hour. The effects on the performance in 1M LiPFsub 6/ethylene carbonate (EC)-dimethyl carbonate (DMC) solutions were evaluated by galvanostatic cycling tests, complex-impedance spectroscopy, and, to a more limited extent, cyclic voltammetry. Partial oxidation of PMAN carbon showed little or no overall beneficial effects in performance relative to the control.